The chilbury ladies' choir eaudiobook A novel. - Ryan, Jennifer (Random House Audio, 2017)
"Just because the men have gone to war, why do we have to close the choir? And precisely when we need it most!"    As England enters World War II's dark early days, spirited music professor Primrose Trent, recently arrived to the village of Chilbury, emboldens the women of the town to defy the Vicar's stuffy edict to shutter the church's choir in the absence of men and instead "carry on singing." Resurrecting themselves as "The Chilbury Ladies' Choir," the women of this small village soon use their joint song to lift up themselves, and the community, as the war tears through their lives. Told through letters and journals, THE CHILBURY LADIES' CHOIR moves seamlessly from budding romances to village intrigues to heartbreaking matters of life and death. As we come to know the struggles of the charismatic members of this unforgettable outfit— a timid widow worried over her son at the front; the town beauty drawn to a rakish artist; her younger sister nursing an impossible crush and dabbling in politics she doesn't understand; a young Jewish refugee hiding secrets about her family, and a conniving midwife plotting to outrun her seedy past— we come to see how the strength each finds in the choir's collective voice reverberates in her individual life. In turns funny, charming and heart-wrenching, this lovingly executed ensemble novel will charm and inspire, illuminating the true spirit of the women on the homefront, in a village of indomitable spirit, at the dawn of a most terrible conflict. This audiobook includes popular versions of classical music sung by women’s choirs, including the songs Abide with Me and All Creatures , Ave Maria , and The Lord's My Shepherd  Cast of Narrators: Gabrielle Glaister Laura Kirman Imogen Wilde Adjoa Andoh Tom Clegg Mike Grady